Upaya Pencegahan Kecurangan Pengelolaan Keuangan Dana Desa Dengan Menggunakan Sistem Audit - Yuyun Suryani (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to examine the influence of the village financial system on the prevention of fraud in the management of village funds using an audit system. In addition, this study also examines whether individual morality can moderate the relationship between the village financial system and the prevention of village fund fraud. Building public trust in the government in managing village funds at this time is quite difficult. Given the current situation, the public must know what performance the government is doing. The lack of transparency in every activity raises various kinds of suspicion. The village APB can also be said to be one of the budgets held within one period by the village. The village fund budget management system can be stated as an activity that gives rise to fraud. In Indonesia, acts of accounting fraud can be classified into several parts, including the private sector and the public sector. Fraud often occurs among government agencies, because government agencies have a complex organizational structure, a complicated bureaucratic system, a low control system, and high pressure, so this issue is a topic that is continuously discussed.